Pengerasan Permukaan Baja Karbon Rendah Melalui Proses Pack Carburizing Dengan Menggunakan Arang Cangkang Kemiri - Napitupulu, Richard Alfonso; Manurung, Maruba; Manurung, Charles S.P.; Peranginangin, Siwan Edi (SPROCKET JOURNAL OF MECHANICAL ENGINEERING, 2023)
The easiest and most frequently used way to increase the surface hardness of the steel while maintaining its inner ductility is the Pack Carburizing process. By using a carburizer from candlenut shell charcoal as a carbon source, sodium carbonate as a catalyst and SAE 20 oil as a cooling medium. The research variables were T1 = 850o C, T2 = 900o C, T3 = 950o C, T4 = 1000o C while the holding time used was 120 minutes. The highest hardness from the research results was found at T3 900o C = 543.8 HV followed by T2 950o C = 542.8 HV, T1 850o C = 529.2 HV, and T4 1000o C = 527.4 HV